The evolution and genetics of Latin American populations - Salzano, Francisco M (Cambridge University Press, 2013)
The human genetic make-up of Latin America is a reflection of successive waves of colonisation and immigration. There have been few works dealing with the biology of human populations at a continental scale, and while much data is available on the genetics of Latin American populations, most information remains scattered throughout the literature. This volume examines Latin American human populations in relation to their origins, environment, history, demography and genetics, drawing on aspects of nutrition, physiology and morphology for an integrated and multidisciplinary approach. The result is a fascinating account of a people characterised by a turbulent history, marked heterogeneity and unique genetic traits. Of interest to students and researchers of genetics, evolution, biological anthropology and the social sciences, this book will also appeal to anyone concerned with the multifaceted evolution of our species and constitutes an important volume not only for anthropological genetics, but also for Latin American research.